Resurrecting the idea of a Christian society - Reno, Russell R., 1959- (Washington, DC : Regnery Faith, 2016)
Taking his cue from T. S. Eliot's famous essay The idea of a Christian society, Reno analyzes how and why he feels America has grown away from being a Christian society and makes the argument to again work toward that ideal--
The need for a Christian society -- Defend the weak -- Raise up the poor -- Promote solidarity -- Limit government -- Seek higher things -- The possibility of a Christian society.
Includes index.
Keywords: Christianity and politics -- United States; Church and the world; Christian life -- United States; Christian life; Christianity and politics; Church and the world; Religion; United States -- Religion; United States